2015
DOI: 10.1371/journal.pone.0117194
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Posterior Corneal Astigmatism According to Axis Orientation of Anterior Corneal Astigmatism

Abstract: PurposeTo investigate the distribution of posterior corneal astigmatism in eyes with with-the-rule (WTR) and against-the-rule (ATR) anterior corneal astigmatism.MethodsWe retrospectively examined six hundred eight eyes of 608 healthy subjects (275 men and 333 women; mean age ± standard deviation, 55.3 ± 20.2 years). The magnitude and axis orientation of anterior and posterior corneal astigmatism were determined with a rotating Scheimpflug system (Pentacam HR, Oculus) when we divided the subjects into WTR and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
33
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
15
33
5
Order By: Relevance
“…Studies also found that with increasing age, the anterior and total corneal steep meridian shifted from WTR to ATR, whereas the posterior corneal steep meridian did not change significantly [6,7,12]. Our study was consistent with the previous findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies also found that with increasing age, the anterior and total corneal steep meridian shifted from WTR to ATR, whereas the posterior corneal steep meridian did not change significantly [6,7,12]. Our study was consistent with the previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…Savini and Naeser [11] have found that neglecting the posterior corneal astigmatism (PCA) had the highest effect on the refractive error after Toric IOL implantation. However, studies on the overall characteristics of PCA and posterior corneal aberration in a large cohort of patients remain rare [5,12]. Data on the status of posterior cornea are of clinical significance to the TCS assessment, cataract surgical parameters setting, and choosing appropriate IOL [1].…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant positive correlation between posterior corneal astigmatism and anterior corneal astigmatism for the high myopia group, especially when the steep meridian was aligned vertically for the anterior corneal surface, which agreed well with the findings of previous studies [10,14]. However, we found no correlation between the magnitude of posterior corneal astigmatism and total corneal astigmatism.…”
Section: Discussionsupporting
confidence: 92%
“…Orientation of PCA is also variable. It may be possible to predict the orientation of the steep meridian of the posterior cornea when the steep meridian of the anterior cornea is vertical (with-the-rule, or WTR), but it is more difficult to predict when the steep meridian of the anterior cornea is horizontal (against-the-rule, or ATR) or oblique, especially in patients with high ATR anterior corneal astigmatism 8,9. Given the above, corneal astigmatism measurements that rely only on measurement of the anterior corneal surface may be poor predictors of the true total corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%